Synthesis of ion-imprinted polymer for selective separation of copper (ii) from metal ions mixture - Nor Asiken, Abdul Wahab; Mohd Sani, Sarjadi; Sazmal Effendi, Arshad; M. M., Yusoff; Rahman, Md. Lutfor (Asian Publication Corporation, 2019)
Ion imprinted polymers (IIPs) draw great attention in various fields because of powerful selectivity to the target metal ions. Thus, the synthesis of copper-ion imprinted polymer (Cu-IIP) was performed by using copper ion and complexing agent rufigallol with ethylene glycol dimethacrylate (EGDMA) and 2,2-azobisisobutyronitrile (AIBN). Aqueous HCl was used to leach Cu2+ ions from the imprinted polymer for creation of cavities of template, which is utilized for cooper ions adsorption with high selectivity. The IIP were characterized using ICP-MS, FE-SEM and also solid state analysis by UV-visible NIR spectroscopy. FT-IR study confirmed the successful complexation of Cu-IIP. The optimum pH was found to be 6 and highest adsorption capacity was estimated about 112.5 mg g-1. Thus, IIP gave good selectivity to copper ions in presence of other transition metals and also IIP can be regenerated for eight times without a subst-antial loss in adsorption capacity.